Dual Oxidase-Derived Reactive Oxygen Species Against Bacillus thuringiensis and Its Suppression by Eicosanoid Biosynthesis Inhibitors - Sajjadian, Seyede Minoo; Kim, Yonggyun (Frontiers in Microbiology, 2020)
Two entomopathogenic bacteria, Xenorhabdus and Photorhabdus, are known to be able to synthesize and secrete eicosanoid biosynthesis inhibitors (EIBs) that can enhance pathogenicity of Bacillus thuringiensis (Bt) against different target insects. Such enhancements can be explained by the suppression of immune responses in the hemocoel by EIBs. However, little is known about the role of EIBs in the defense against Bt pathogenicity in the gut. This study was focused on the role of insect gut immunity in the defense against Bt pathogenicity, in which the cooperative effect of bacterial metabolites was assessed. Screening 14 different bacterial strains, bacterial culture broth of Photorhabdus temperata subsp. temperata ANU101 (Ptt) gave the highest cooperative effect on Bt virulence along with significant inhibitory activity against phospholipase A2 (PLA2) of Plutella xylostella. In gut lumen, Ptt culture broth suppressed the generation of reactive oxygen species (ROS) induced by Bt treatment and facilitated bacterial growth, similar to vitamin E, an antioxidant. To analyze the ROS source, dual oxidase (Px-Duox) and NADPH-dependent oxidase (Px-Nox) genes were predicted from P. xylostella genome and their expressions were confirmed in larval gut. RNA interference (RNAi) of Px-Duox expression reduced ROS levels in both gut epithelium and lumen while RNAi of Px-Nox expression reduced ROS levels only in gut epithelium. Ptt extract significantly suppressed gene expression levels of Px-Duox and Px-Nox, leading to lower ROS concentrations in the gut lumen. Three commercial PLA2 inhibitors significantly increased the insecticidal activity of Bt by suppressing ROS levels in the gut lumen. These results indicate that Ptt extract containing EBIs can prevent up-regulation of ROS level in the midgut in response to Bt infection and enhance the virulence of Bt against P. xylostella.